2004
DOI: 10.1029/2004gb002228
|View full text |Cite
|
Sign up to set email alerts
|

Dust deposition pulses to the eastern subtropical North Atlantic gyre: Does ocean's biogeochemistry respond?

Abstract: [1] Enhancement of primary and export production following dust deposition pulses is well established for High Nutrient Low Chlorophyll regions, but the effect of atmospheric dust on the biogeochemistry of oligotrophic gyre regions remains unclear.Here we report atmospheric dust concentrations measured on Gran Canaria, Canary Islands, concomitantly with upper water biogeochemistry at the oligotrophic time series station ESTOC (European Station for Time series in the Ocean, Canary Islands) during a 2-year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
62
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 45 publications
4
62
2
Order By: Relevance
“…A recent study demonstrated that the most frequent and intense response of the microbial plankton to atmospheric dust deposition in the Tropical Atlantic is the stimulation of the bacterial activity rather than phytoplankton primary production (Marañón et al, 2010). This is consistent with the results found at ESTOC, which is strongly influenced by the natural atmospheric deposition of Saharan dust, and where phytoplanktonic production seems not to be affected by aerosol inputs (Neuer et al, 2004).…”
Section: Introductionsupporting
confidence: 81%
“…A recent study demonstrated that the most frequent and intense response of the microbial plankton to atmospheric dust deposition in the Tropical Atlantic is the stimulation of the bacterial activity rather than phytoplankton primary production (Marañón et al, 2010). This is consistent with the results found at ESTOC, which is strongly influenced by the natural atmospheric deposition of Saharan dust, and where phytoplanktonic production seems not to be affected by aerosol inputs (Neuer et al, 2004).…”
Section: Introductionsupporting
confidence: 81%
“…Towards 12 • N, upwelling is also fed by the North Equatorial Undercurrent (Hagen and Schemainda, 1984). Moreover, the entire northwest African coast is also influenced by the African desert dust transport by the midtropospheric Harmattan winds originating from the central Sahara, which supplements the levels of micronutrients (such as iron) to the adjacent marine ecosystem (Mittelstaedt, 1983;Neuer et al, 2004). The study area is also affected by the migration of the Intertropical Convergence Zone (ITCZ), related to maximum precipitation rates (Hastenrath, 1995).…”
Section: Physical Propertiesmentioning
confidence: 99%
“…iron) and macronutrients to the ocean surface waters (e.g. Jickells et al, 2005;Neuer et al, 2004). Additionally, dust acts as ballast mineral (Armstrong et al, 2002;Klaas and Archer, 2002) for organic carbon-rich particles (e.g.…”
Section: Introductionmentioning
confidence: 99%